Transitioning from pediatric to adult healthcare with an inborn error of immunity: a qualitative study of the lived experience of youths and their families - Ouimet, François; Fortin, Justine; Bogossian, Aline; Padley, Nicole; Chapdelaine, Hugo; Racine, Eric (Frontiers in Immunology, 2023)
Transition from pediatric to adult healthcare is a multifaceted and consequential process with important health implications for youth. Although research on transition has grown significantly, research on transition for patients living with an inborn error of immunity (IEI) is scarce. We undertook a qualitative study to better understand the perspectives of youths and parents in an outpatient immunology clinic. Semi-structured interviews were conducted with 9 youths, 6 parents and 5 clinicians, all recruited from the same clinic. All youths recently transferred to adult care with or without an established diagnosis of IEI. Interviews were transcribed verbatim and thematic analysis was conducted. Two sets of themes were generated. The first set captured the positive and negative aspects experienced during transition, as well as recommendations to facilitate the process. The second set focused on key topics discussed in the interviews that were merged into overarching themes. Perspectives of participants were clustered into 6 overarching themes: (1) lack of knowledge about IEIs; (2) scattered transitions; (3) changing healthcare teams; (4) approaching an unknown environment; (5) transitioning to adulthood; (6) assuming responsibility for the management of the condition. Overall, the challenges encountered with respect to these themes had profound clinical and humanistic implications for patients such as generating significant distress. We discuss the unique challenges of the youths in our study in comparison to common problems reported by youths with chronic illness in the broader transition literature (for example: the change of healthcare team, the lack of information about the transition process and navigating the adult care system, growth towards self-management and the co-occurring developmental transition to adulthood). There is an urgency to attend to the specific problems created by the rarity of IEIs and related lack of knowledge about them as well as the need for multidisciplinary cross-clinic care during transition and beyond.